REFORMULATION OF THE SOCIAL SAFETY NET: A CONCEPTUAL APPROACH BASED ON QUR’ANIC VALUES - Hidayati, Tri Wahyu (Balai Penelitian dan Pengembangan Agama Semarang, 2022)
This paper aims to find out a conceptual approach to the social safety net in the Qur’an and some essential values that can be realized as role models in contemporary modern life. This study investigates several significant questions, such as how the Qur'an argues for taking sides with the disadvantaged people, and what instruments are outlined by the Qur'an as the main support for the implementation of social safety nets. These questions are approached contextually and critically by examining primary texts, such as verses of the Qur'an that talk about the topic, to be interpreted thematically-contextually. Meanwhile, secondary texts are used as interpretive supports to enrich perspectives in reconstructing and reformulating the idea of a social safety net based on the Qur'anic values. This study concludes; first, even though the Qur’an does not mention explicitly the term social safety net, the teachings of the social safety net are implicitly embodied in the Qur’an. Second, some fundamental instruments in the Qur’an can be realized as supporting systems for social safety nets, such as zakah, kafarat, infaq, sadaqah, qurban, dam and fidyah, fai’, and ghanimah. Third, the Qur’anic concept of social safety net engages with five principles, namely expanse and balance, justice and equity, spirituality and productivity, sustainability and empowerment, and dynamic and systematic. Thus, the concept of the social safety net in the Qur’an is a comprehensive approach, not only for the short term but also for the long term, not only consumptive-giving but also productive-empowering.